2016
DOI: 10.1155/2016/3648719
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Lactoferrin Modulates PGE2, MMP-9, MMP-2, and TIMP-1 Amniotic Fluid Concentrations

Abstract: Inflammation plays an important role in pregnancy, and cytokine and matrix metalloproteases (MMPs) imbalance has been associated with premature rupture of membranes and increased risk of preterm delivery. Previous studies have demonstrated that lactoferrin (LF), an iron-binding protein with anti-inflammatory properties, is able to decrease amniotic fluid (AF) levels of IL-6. Therefore, we aimed to evaluate the effect of vaginal LF administration on amniotic fluid PGE2 level and MMP-TIMP system in women undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
(52 reference statements)
1
10
0
1
Order By: Relevance
“…Therefore, the in vivo finding that women administered with LF 12 h before amniocentesis had levels of TAS and OSI comparable with controls, but still a significant MDA-lowering activity, may be due to the short in vivo half-life of the protein ( 15 ). This is in line with our previous observations indicating that LF seems more effective at 4 h rather than 12 h of administration ( 16 , 17 ). Thus, from a mechanistic point of view, once LF enters the amniotic compartment it can decrease the formation of lipoperoxides by directly scavenging intermediary ROS, or by “removing” Fe 3+ from the Fenton reaction ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, the in vivo finding that women administered with LF 12 h before amniocentesis had levels of TAS and OSI comparable with controls, but still a significant MDA-lowering activity, may be due to the short in vivo half-life of the protein ( 15 ). This is in line with our previous observations indicating that LF seems more effective at 4 h rather than 12 h of administration ( 16 , 17 ). Thus, from a mechanistic point of view, once LF enters the amniotic compartment it can decrease the formation of lipoperoxides by directly scavenging intermediary ROS, or by “removing” Fe 3+ from the Fenton reaction ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…Lactoferrin easily fulfill these criteria. In fact, our previous studies demonstrated that LF administration is able to modulate inflammatory markers in the amniotic fluid, including the detrimental MMPs connected to pre-labor rupture of membranes (PROM) and PPROM (16,17). In addition, there is overwhelming evidence that LF can normalize insult-induced reactions due to immune modulation properties (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost the same results were obtained by Locci et al [102] in a longitudinal study where intravaginal bLf treatment, consisting of 300 mg bLf for 21 days in asymptomatic women at low risk for PTD, was effective in lowering cervico-vaginal IL-6 levels and improving cervical length [102]. Moreover, in other studies, conducted on pregnant women showing high levels of pro-inflammatory mediators in AF, a single intravaginal bLf administration (300 mg), 4 h or 12 h before amniocentesis, was surprisingly efficient in partially decreasing some mediators of pro-inflammatory processes, including IL-6 [110,111,112].…”
Section: Lactoferrin Against Aseptic Inflammationmentioning
confidence: 99%
“…We found that vaginal lactoferrin significantly lowers PGE 2, active MMP-9, and its inhibitor TIMP-1. Conversely, active MMP-2 and MMP-2/TIMP-2 molar ratio are increased, whilst TIMP-2 remains unchanged [60].…”
Section: Lactoferrinmentioning
confidence: 93%